The methamphetamine crisis: strategies to save addicts, families and communities - Covey, Herbert C. (Praeger, 2007)
Foreword / by Lori Moriarty -- The basics of methamphetamine -- What is methamphetamine and how and why is it used? / Herbert Covey -- Prevalence of use and manufacture of methamphetamine in the United States : is the sky falling or is it not really a problem? / Herbert Covey -- The human side to clandestine meth labs and health risks of exposure -- Methamphetamine production : lab identification and the dangers of making meth to families, children, and professionals / Lynn Riemer -- The short- and long-term medical effects of methamphetamine on children and adults / Kathryn Wells -- The environmental clean-up of methamphetamine labs / Colleen Brisnehan -- Case management and treatment for meth use : does anything work? -- Case planning with parents affected by methamphetamine addiction / Karen Mooney -- Community based treatment for methamphetamine addiction / Nicolas Taylor -- A multi-site comparison of psychosocial approaches for the treatment -- Of methamphetamine dependence / Richard A. Rawson -- Child welfare and methamphetamine / Herbert Covey -- My story: words of experience from a methamphetamine addict in recovery / Tonya Wheeler -- Samantha's story : words of experience from a methamphetamine addict in recovery / Samantha Cameron -- Mother of a meth addict / Rhonda -- Community and legal responses to meth use and manufacture -- Methamphetamine addiction : an integrated approach to case management, evaluation, and treatment / Angela Mead -- Drug courts : an effective strategy for communities facing methamphetamine / C. West Huddleston III -- A creative partnership among multiple systems : the El Paso County, Colorado, family treatment drug court / Shirley Rhodus and Julia Roguski